Sustainable mining of pozzolana in Uganda - Naigaga, Eunice (Kampala, 2015)
Unpublished Thesis (PHD) - Makerere University, 2015
Includes bibliographical references (p. 163-171)
Keywords: Mining engineering -- Uganda